Penilaian Kerusakan Jalan pada Ruas Jalan Mojopurno Dimong Kabupaten Madiun dengan Metode Bina Marga - Pratama, Andra Satria; Aditya, Rizky; Hartatik, Nurani (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The decline in road pavement quality due to service age, traffic load, and environmental factors requires planned handling through condition assessment using the Bina Marga method and the 2024 Pavement Design Manual reference. Research on the Mojopurno–Dimong Road Section in Madiun Regency uses LHR data, Benkelman Beam deflection tests, and field observations to analyze structural conditions and determine treatment needs. The results of the study are expected to produce effective, efficient, and sustainable technical recommendations to improve road performance and service life.